Platelet Aggregation in Diabetes Mellitus and the Effect of Insulin in Vivo on Aggregation - Hassanein, A. A; El-Garf, Th. A; El-Baz, Z (Thrombosis and Haemostasis, 1972)
ADP-induced platelet aggregation and calcium-induced platelet aggregation tests were studied in 14 diabetic patients in the fasting state and half an hour after an intravenous injection of 0.1 unit insulin/kg body weight. Platelet disaggregation was significantly diminished as compared to a normal control group, and their results were negatively correlated with the corresponding serum cholesterol levels. Insulin caused significant diminution in the ADP-induced platelet aggregation as a result of rapid onset of aggregation and disaggregation. There was also a significant increase in platelet disaggregation. In the calcium-induced platelet aggregation test, there was a significant shortening of the aggregation time, its duration, and the clotting time. The optical density fall due to platelet aggregation showed a significant increase. Insulin may have a role in correcting platelet disaggregation possibly through improvement in the intracellular enzymatic activity.